TABOO VALUES IN WULLA PODDU 'PAMALI MONTH' THE LOLI COMMUNITY BELIEVES IN MARAPU AND THE IMPORTANCE OF TEACHING IT IN PRIMARY SCHOOLS - Djawa, Alex; Juli, Labu (Academic Journal of Educational Sciences, 2023)
The lives and living habits of the Loli people who believe in Marapu are greatly influenced by their trust and confidence in Marapu. One of the socio-cultural events held every year is Wulla Poddu 'Pemali month'. This month there are many cultural events taking place. Apart from that, there are taboo things that are not permitted or prohibited. These things include: not being allowed to cut down large trees (the value of obedience), not being allowed to cut down large animals, such as buffalo, horses, cows and pigs. More than two people are not allowed to carry wood, they are not allowed to pound rice, fight wood or shout at night. (social and cultural values)